2012
DOI: 10.4141/cjps2011-054
|View full text |Cite
|
Sign up to set email alerts
|

Sugar beet (Beta vulgaris L.) storage quality in large outdoor piles is impacted by pile management but not by nitrogen fertilizer or cultivar

Abstract: beet (Beta vulgaris L.) storage quality in large outdoor piles is impacted by pile management but not by nitrogen fertilizer or cultivar. Can. J. Plant Sci. 92: xxxÁxxx. Even though storage results in lower sucrose recovery from sugar beets, physical constraints dictate that a significant proportion of the sugar beet crop can be stored up to 120 d before processing. From 2006From to 2010 (1 ), sugar beet cultivar, and pile management method were independently evaluated to determine their effects on sugar bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…A moderate supply of nitrogen fertilizer is an essential limiting factor for optimum yield, but the excess in nitrogen fertilizer amounts may result in an increase in root yield with lower sucrose content and juice purity [4][5][6][7]. Over fertilizing sugar beet with more nitrogen than needed for maximum sucrose production led to decreased sucrose yield [8,9]. With increasing nitrogen supply, sugar concentration decreased, while root yield, sugar yield, and white sugar yield increased and reached maximum values when sugar beet was fertilized at 159, 136, and 129 kg N/ha, respectively [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate supply of nitrogen fertilizer is an essential limiting factor for optimum yield, but the excess in nitrogen fertilizer amounts may result in an increase in root yield with lower sucrose content and juice purity [4][5][6][7]. Over fertilizing sugar beet with more nitrogen than needed for maximum sucrose production led to decreased sucrose yield [8,9]. With increasing nitrogen supply, sugar concentration decreased, while root yield, sugar yield, and white sugar yield increased and reached maximum values when sugar beet was fertilized at 159, 136, and 129 kg N/ha, respectively [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted where it was concluded that fertilizing sugar beet with too little nitrogen resulted in the reduction of root tonnage and, conversely, the application of too much resulted in reduced sucrose concentrations and purity percentage [4][5][6][7]. Although deficient nitrogen content in the soil can reduce sugar beet root yield, excess amounts of N can decrease sucrose content while lowering sucrose recovery due to higher nitrate impurities [8,9]. In England, sugar beets are fertilized using 100-110 kg N/ha as an equilibrating rate between fertilizer prices and beet value [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is an innovative, not yet described in the literature, way of storing sugar beet as a potential biomaterial for energy production, which does not require building storage lagoons, does not take up the land that could be otherwise used for cultivation and thus reduces investment costs. However, storing sugar beet pulp in open storage lagoons for energy purposes is commonly used, for instance, by German agricultural biogas plants [34,35]. Nonetheless, such a method has its drawbacks, the chief one being the loss of organic and mineral matter from the stored biomass, as reported in the literature [28,36].…”
Section: Preparation For the Researchmentioning
confidence: 99%
“…As the storage period was extended (by another 8, 16 and 32 weeks), the decomposition of the organic matter took place-both in the sugar beet stored in airtight conditions and in the pulp stored in an open-air container. After 8 and 16 weeks of storage, the biogas efficiency was increased: 139 35. mL•g −1 FM-H, 144.14 mL•g −1 FM-O, 147.58 H mL•g −1 FM-H and 148.22 mL•g −1 FM-O, respectively.…”
mentioning
confidence: 98%
“…However, given the significant losses currently suffered in storage in Idaho, host resistance and cultivar selection alone are not enough to deal with storage problems (9,12,26,46). Currently, physical control practices such as tarping, ventilation, and stripping the outer meter of sugar beet roots from the pile surface are utilized to reduce storage losses (6,37,38,57). Although these physical methods reduce sucrose losses, additional control measures for storage such as chemical treatments have been investigated (1,12,23,31,32,61).…”
mentioning
confidence: 99%